CeO2 Structure Adjustment by H2O via the Microwave–Ultrasonic Method and Its Application in Imine Catalysis - Chang, Xijiang; Ding, Huihui; Yang, Jingxia (Frontiers in Chemistry, 2022)
CeO2 with fusiform structures were prepared by the combined microwave–ultrasonic method, and their morphologies and surface structure were changed by simply adding different amounts of H2O (1–5 ml) to the precursor system. The addition of H2O changed the PVP micelle structure and the surface state, resulting in CeO2 with a different specific surface area (64–111 m2 g−1) and Ce3+ defects (16.5%–28.1%). The sample with 2 ml H2O exhibited a high surface area (111.3 m2∙g−1) and relatively more surface defects (Ce3+%: 28.1%), resulting in excellent catalytic activity (4.34 mmol g−1 h−1).